Measuring quality in colorectal cancer surgery in low- and middle-income countries: The Clavien-Dindo classification in a Sri Lankan cohort. (July 2022) - Lindholm, S.; Lindskogen, S.; Gamage, B.; Kurlberg, G.; Ljungman, D.
Abstract: Background: The colorectal cancer (CRC) incidence is increasing in low- and middle-income countries (LMICs) as part of an ongoing epidemiological transition. Surgery is the main treatment and surgical services are scaled up to meet the need. This warrants the establishment of frugal systems to measure safety and quality of surgical care that are tailored for low-resource settings. The aim of this study was to test the applicability of the Clavien-Dindo classification (CDC) for measurement of surgical complications in an LMIC setting where medical records are paper-based. Material and methods: 88 patients who underwent CRC resection at Colombo South Teaching Hospital, Sri Lanka, from January 2017 to January 2020 were included. Medical records were retrospectively reviewed for postoperative complications and the severity was graded using the CDC. Results: One or more postoperative complications (CDC ≥ grade II) occurred in 45.5% (n = 40) of the patients. The complications were distributed as grade II n = 46, grade III n = 3, grade IV n = 2 and grade V n = 0. The most common complication (22.7%, n = 20) was postoperative anemia treated with blood transfusion. The second most common complication was incisional surgical site infection (11.4%, n = 10). Conclusion: Postoperative outcome could be evaluated by using the CDC in a Sri Lankan facility based on retrospective review of medical records. This suggests that the CDC is a feasible standardized system appropriate for measuring surgical quality also in other LMICs. Identified fields for possible quality improvement at the study site were to limit blood transfusions and minimize treatment with antibiotics. Graphical abstract: Image 1 Highlights: Global health is putting focus on not only access to surgery, but also surgical quality and safety. The Clavien-Dindo Classification may be a standardized way of evaluating surgical quality in low-resource settings. The feasibility of Clavien-Dindo Classification in a retrospective cohort in Sri Lanka is demonstrated.